Prioritization of factors affecting surface roughness of wood and wood-based materials in CNC machining: a fuzzy analytic hierarchy process model. Issue 2 (4th March 2022) - Singer, Hilal; Özşahin, Şükrü
ABSTRACT: In this study, the fuzzy analytic hierarchy process was employed to prioritize some factors affecting the surface roughness of wood and wood-based materials in CNC machining. Within the model, four main factors and eighteen subfactors were defined. After constructing the hierarchical structure, the factors were analyzed through experts' opinions. The results demonstrated that wood properties and machining parameters were the most significant main factors. Furthermore, density was found to be the most important subfactor. Consequently, the findings of this study will help the wood industry in enhancing the surface quality of final products.